The Role of Smartphones in Learning English (Eight Students For English Study Program of Stkip Setia Budhi Rangkasbitung) - Dita Nur Alma Syofin; Habib Cahyono; Obay Jambari (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2022)
Abstract: This research was conducted to see how the role of smartphones in learning English for the eighth semester at STKIP Setia Budhi Rangasbitung. Especially trying to find out the role of smartphones through zoom meetings in during the pandemic. The method used in this study was a qualitative method with questionnaire and interview instruments. four students were selected to investigate the role of smartphones through zoom meetings in learning. The Data were gathered through instruments Questionnaire and structured interviews. The result of study showed that the part of smartphones through Zoom gatherings for learning exercises can give more encounters for understudies where understudies can be associated specifically, understudies can be conducted address and reply discourses and introductions almost the learning issues they are confronting, and online learning can run easily and get most extreme.